Hidden diversity of Pestalotiopsis and Neopestalotiopsis (Amphisphaeriales, Sporocadaceae) species allied with the stromata of entomopathogenic fungi in Taiwan - Sheng-Yu Hsu; Yuan-Cheng Xu; Yu-Chen Lin; Wei-Yu Chuang; Shiou-Ruei Lin; Marc Stadler; Narumon Tangthirasunun; Ratchadawan Cheewangkoon; Hind A Al-Shwaiman; Abdallah M Elgorban; Hiran A Ariyawansa (My University, 2024)
Pestalotiopsis sensu lato , commonly referred to as pestalotiopsis-like fungi, exhibit a broad distribution and are frequently found as endophytes, saprobes and pathogens across various plant hosts. The taxa within pestalotiopsis-like fungi are classified into three genera viz. Pestalotiopsis , Pseudopestalotiopsis and Neopestalotiopsis , based on the conidial colour of their median cells and multi-locus molecular phylogenies. In the course of a biodiversity investigation focusing on pestalotiopsis-like fungi, a total of 12 fungal strains were identified. These strains were found to be associated with stromata of Beauveria , Ophiocordyceps and Tolypocladium in various regions of Taiwan from 2018 to 2021. These strains were evaluated morphologically and multi-locus phylogenetic analyses of the ITS (internal transcribed spacer), tef1-α (translation elongation factor 1-α) and tub2 (beta-tubulin) gene regions were conducted for genotyping. The results revealed seven well-classified taxa and one tentative clade in Pestalotiopsis and Neopestalotiopsis . One novel species, Pestalotiopsis manyueyuanani and four new records, N. camelliae-oleiferae , N. haikouensis , P. chamaeropis and P. hispanica , were reported for the first time in Taiwan. In addition, P. formosana and an unclassified strain of Neopestalotiopsis were identified, based on similarities of phylogeny and morphology. However, the data obtained in the present study suggest that the currently recommended loci for species delimitation of pestalotiopsis-like fungi do not deliver reliable or adequate resolution of tree topologies. The in-vitro mycelial growth rates of selected strains from these taxa had an optimum temperature of 25 °C, but growth ceased at 5 °C and 35 °C, while all the strains grew faster under alkaline than acidic or neutral pH conditions. This study provides the first assessment of pestalotiopsis-like fungi, associated with entomopathogenic taxa.
Keywords: Pestalotiopsis; Beauveria; Intergenic region; Dothideomycetes; Colletotrichum; Plant Pathogens and Fungal Diseases